Gemini/GMOS imaging of globular cluster systems in five early-type galaxies - Faifer, Favio Raúl (2011)
In this paper, we present deep high-quality photometry of globular cluster systems (GCSs) belonging to five early-type galaxies, covering a range of mass and environment. Photometric data were obtained with the Gemini North and Gemini South telescopes in the filter passbands g', r' and i'. The combination of these filters with good seeing conditions allows an excellent separation between globular cluster (GC) candidates and unresolved field objects. In fact, our previously published spectroscopic data indicate a contamination level of only ~10 per cent in our sample of GC candidates. Bimodal GC colour distributions are found in all five galaxies. Most of the GCSs appear bimodal even in the (g'-r') versus (r'-i') plane. A population of resolved/marginally resolved GC and ultracompact dwarf candidates was found in all the galaxies. A search for the so-called 'blue tilt' in the colour-magnitude diagrams reveals that NGC 4649 clearly shows this phenomenon, although no conclusive evidence was found for the other galaxies in the sample. This 'blue tilt' translates into a mass-metallicity relation given by Z∝M0.28 ±0.03. This dependence was found using a new empirical (g'-i') versus [Z/H] relation, which relies on an homogeneous sample of GC colours and metallicities. In this paper, we also explore the radial trends in both colour and surface density for the blue (metal-poor) and red (metal-rich) GC subpopulations. As usual, the red GCs show a steeper radial distribution than the blue GCs. Evidence of galactocentric colour gradients is found in some of the GCSs, which is more significant for the two S0 galaxies in the sample. Red GC subpopulations show similar colours and gradients to the galaxy halo stars in their inner region. A GC mean colour-galaxy luminosity relation, consistent with [Z/H]∝L0.26 ±0.08B, is present for the red GCs. Estimates of the total GC populations and specific frequency SN values are presented for NGC 3115, 3923 and 4649.